Examining Indonesian Gen Z Muslim Consumers' Purchase Intentions for Muslim Fashion on Shopee: A TPB Extension Perspective - Fortunata, Sabrina; Hanafiah, Ali (Jurnal Ilmiah Manajemen dan Bisnis, 2024)
Shopee is the leading online shopping platform in Southeast Asia and Taiwan. Currently, there is competition in the Islamic market through e-commerce. The purpose of this study was to examine and analyze the effect of e-wom, product quality, attitudes, subjective norms, and perceived behavioral control on the purchase intention of shopee e-commerce. The object of this research is Generation Y and Z Muslim women in Indonesia asmany as 231 respondents. The approach used in this research is quantitative. From the PLS-SEM data analysis method, with analysis tool Smart-PLS 3.2.9., it show that e-wom has a positive and significant effect on purchase intention, and quality product has a positive and significant effect on purchase intention. Moreover, the initial predictor variables derived from TPB (attitude, subjective norms, perceived behavioral control) continue to exhibit a positive correlation with the behavioral intention to purchase Muslim fashion among Generation Z individuals in Indonesia, aligning with the original TPB theory.